2022
DOI: 10.1002/cam4.5278
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sarcopenia on survival and treatment tolerance in patients with head and neck cancer treated with chemoradiotherapy

Abstract: Background: Sarcopenia appears to be a negative prognostic factor for poor survival outcomes and worse treatment tolerance in patients with head-and-neck squamous cell carcinoma (HNSCC). We evaluated sarcopenia's impact on overall survival (OS), disease-free survival (DFS) and chemo-radiation tolerance in patients with head-and-neck cancer (HNC) treated with chemoradiotherapy (CRT) from a monocentric observational study. Methods:We identified patients with HNC treated by CRT between 2009 and 2018 with pretreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Muscle atrophy, characterized by the loss of mass and function in skeletal muscles resulting from an imbalance between protein synthesis and breakdown, encompasses conditions such as muscle malnutrition, muscle-wasting syndrome, and cachexia [4][5][6]. Diverse causes of muscle atrophy include insufficient physical activity, aging, disease, excessive stress, hormonal changes, and congenital factors [4,[7][8][9][10][11][12]. In contemporary medical discourse, muscle atrophy is defined as a pathological degenerative condition that negatively affects the quality of life and contributes to the mortality and morbidity of various diseases [4,13].…”
Section: Introductionmentioning
confidence: 99%
“…Muscle atrophy, characterized by the loss of mass and function in skeletal muscles resulting from an imbalance between protein synthesis and breakdown, encompasses conditions such as muscle malnutrition, muscle-wasting syndrome, and cachexia [4][5][6]. Diverse causes of muscle atrophy include insufficient physical activity, aging, disease, excessive stress, hormonal changes, and congenital factors [4,[7][8][9][10][11][12]. In contemporary medical discourse, muscle atrophy is defined as a pathological degenerative condition that negatively affects the quality of life and contributes to the mortality and morbidity of various diseases [4,13].…”
Section: Introductionmentioning
confidence: 99%
“…Tolerance to surgery, radiation, and chemotherapy decrease because of compromised muscle mass. At cancer diagnosis up to 46-49% of patients suffer from sarcopenia (Bentahila et al, 2023). Variability exists in the prevalence of sarcopenia among patients with cancer depending on the type of cancer, metastasis (if present), disease stage, and diet quality.…”
Section: Introductionmentioning
confidence: 99%
“… 11 These negative outcomes include chemotherapy-related toxicities, 12 high risk of postoperative complications, 13 early treatment discontinuation, 14 and increased mortality rates. 12 , 15 Additionally, patients undergoing (chemo)radiation therapy often encounter notable decreases in skeletal muscle mass, muscle strength, physical activity (PA) levels, fatigue regulation, and overall quality of life during and after the treatment course. 16 A previous study 17 reported that 8.5% of patients with HNC attained the recommended levels of exercise following their treatment.…”
Section: Introductionmentioning
confidence: 99%